Extended Endoscopic Endonasal Approach for Tuberculum Sella Meningiomas: Lessons Learned - Yerragunta, Thirumal; Yerramneni, Vamsi Krishna; Kanala, Ram Nath Reddy; Rangan, Vasundhara; Karanth, Vishwa Kumar K S; Shahid, Mohammed; Akurati, Sri Venkata Sasank; Rao Mahendrakar, Dasagriva (Nepal Journal of Neuroscience, 2024)
Midline meningiomas arising from the anterior skull base, particularly the planum sphenoidale and tuberculum sellae (TSM), present unique challenges due to their proximity to vital structures such as the optic apparatus. Traditionally approached via transcranial routes, these lesions often lead to chronic compression of optic nerves, resulting in visual impairment. With advancements in endoscopic skull base surgery, extended endonasal endoscopic (EEE) approaches have emerged as a viable alternative. This study aims to analyze the technical nuances and outcomes of EEE approach for excision of anterior skull base meningiomas presenting with visual impairment. Thirteen patients with TSM and visual impairment underwent EEE surgery at a single institute. Clinical, radiological, and ophthalmological evaluations were conducted pre- and post-operatively. Surgical techniques involved meticulous tumor excision, preservation of vital structures, and multi-layer skull base reconstruction. Visual outcomes, extent of resection, complications, and endocrine function were assessed. The study demonstrated significant visual improvement in 76.9% of patients, with no cases of permanent visual deterioration. Complete tumor excision was achieved in the majority, with near-total excision in selected cases due to adhesions or tumor characteristics. Complications included CSF rhinorrhea, meningitis, and transient visual field defects, all managed effectively. Endocrine function remained largely unaffected postoperatively, except for one case of diabetes insipidus. The EEE approach offers distinct advantages in accessing and excising anterior skull base meningiomas, particularly in achieving optic nerve decompression while preserving vision. Despite challenges associated with larger tumors and adhesions, careful surgical planning and techniques can optimize outcomes. This study contributes to the growing evidence supporting the efficacy and safety of EEE approaches in treating anterior skull base meningiomas, emphasizing the importance of surgical expertise and patient selection.